Metal-organic frameworks : design and application - MacGillivray, Leonard R. (John Wiley & Sons, 2010)
Metal-organic frameworks represent a new class of materials that may solve the hydrogen storage problem associated with hydrogen-fueled vehicles. In this first definitive guide to metal-organic framework chemistry, author L. MacGillivray addresses state-of-art developments in this promising technology for alternative fuels. Providing professors, graduate and undergraduate students, structural chemists, physical chemists, and chemical engineers with a historical perspective, as well as the most up-to-date developments by leading experts, Metal-Organic Frameworks examines structure, symmetry.